2019
DOI: 10.1021/jacs.9b07072
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Computational Studies of a Series of Terphenyl Substituted Diplumbynes with Ligand Dependent Lead–Lead Multiple-Bonding Character

Abstract: A series of formally triply bonded diplumbyne analogues of alkynes of the general formula ArPbPbAr (Ar = terphenyl ligand with different steric properties) was synthesized by two routes. All diplumbyne products were synthesized by a simple reduction of the corresponding Pb(II) halide precursor ArPb(Br) by DIBAL-H with yields in the range 8−48%. For one of the diplumbynes Ar Pri 4 PbPbAr Pri 4 (Ar Pri 4 = C 6 H 3 -2,6-(C 6 H 3 -2,6-Pr i 2 ) 2 ) it was shown that reduction of Ar Pri 4 Pb(Br) using a magnesium(I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…After this discovery, several research groups independently reported the synthesis of phosphasilenes depicted in Figure 5 (96)(97)(98)(99)(100). [72b-f,73] Recently, Scheschkewitz et al [74a] synthesized cyclic phosphasilene by the reaction of disilenide (101) with NHC-stabilized P(I) cation (102) (1 : 1 ratio) led to the formation of donorstabilized cyclic phosphasilene (103, Scheme 35).…”
Section: Phosphasilenes (> Si=pà )mentioning
confidence: 99%
See 1 more Smart Citation
“…After this discovery, several research groups independently reported the synthesis of phosphasilenes depicted in Figure 5 (96)(97)(98)(99)(100). [72b-f,73] Recently, Scheschkewitz et al [74a] synthesized cyclic phosphasilene by the reaction of disilenide (101) with NHC-stabilized P(I) cation (102) (1 : 1 ratio) led to the formation of donorstabilized cyclic phosphasilene (103, Scheme 35).…”
Section: Phosphasilenes (> Si=pà )mentioning
confidence: 99%
“…Recently, Grimme, Power and co‐workers isolated a formally triple bonded terphenyl substituted diplumbyne analogue of alkynes by a simple reduction of the corresponding Pb(II) halide precursor by DIBAL−H [102] . The sterically crowded diplumbyne Ar Pri8 PbPbAr Pri8 (Ar Pri8 =C 6 H‐3,5‐Pr i 2 ‐2,6‐(C 6 H 2 ‐2,4,6‐Pr i 3 ) 2 ) displayed the shortest Pb−Pb bond with a length of 3.0382(5) Å and wide Pb−Pb−C angles of 114.73(7)° and 116.02(6)°, consistent with the multiple‐bond character, with a bond order up to 1.5.…”
Section: Tin and Lead Multiple Bondmentioning
confidence: 99%
“…Recent studies by Power and co‐workers showed the reversibility of distannyne–stannylene in toluene solutions [111] as well as the reversibility of dihydrogen activation by distannynes [112] . Despite diplumbylenes being the first example of a heavier E 14 –E 14 triple bond, it was only recently that further examples emerged [113] . A combined experimental and theoretical study found that London dispersion forces [31] were important in the stabilisation of diplumbylenes.…”
Section: Group 14 Multiple Bondsmentioning
confidence: 99%
“…Those which are less trans ‐bent contain increased multiple bond character compared with their more trans ‐bent counterparts (i.e. closer to 90°) [113] …”
Section: Group 14 Multiple Bondsmentioning
confidence: 99%
See 1 more Smart Citation